ANALISIS KEBIJAKAN KURIKULUM DI SEKOLAH DASAR (TINJAUAN KURIKULUM 13 HINGGA KURIKULUM MERDEKA) - Dimas Agung Prayoga; MUH WASITH ACHADI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract Balancing the curriculum is very important to do, except for balancing the curriculum in elementary schools to improve the quality of educational processes and outcomes. The purpose of this research is to find out how to balance the curriculum in elementary schools in the education unit level curriculum, the 2013 curriculum, and the policy on independent learning. This research method is descriptive qualitative. Data collection was carried out by means of a literature study. The research results show that the balancing of the elementary school curriculum occurs in harmony with the course of Indonesian history. The elementary school curriculum is a competency-based curriculum designed in the KBK, KTSP and 2013 Curriculum, and independent learning. The aims of the research were (1) to find out the differences between the 2013 Curriculum and the Meirdeika Curriculum, (2) to compare the 2013 Curriculum and the Meirdeika Curriculum in elementary schools, as well as (3) to analyze the difficulties encountered in implementing the 2013 Curriculum and the Meirdeika Curriculum in elementary schools. The characteristics of the elementary school curriculum in the 2013 curriculum are a cross curriculum or integrated curriculum for all grades with a scientific approach and authentic assessment. The elementary school curriculum in the study of independent ethics needs to pay attention to designing curriculum ideas, planning national exams, designing lesson plans, and teaching profession. Meanwhile, the implementation of independent learning must include objectives, flexibility, and usability of the curriculum.